The Work Stress of Millennial Employees Reviewed from the Viewpoint of Organizational Climate with Team-Member Exchange as a Moderator [Stres Kerja Karyawan Milenial Ditinjau dari Iklim Organisasi dengan Team-Member Exchange sebagai Moderator] - Muhammad Farie Ath Thaariq; Indrayanti Indrayanti (ANIMA Indonesian Psychological Journal, 2021)
This study aims to define the role of organizational climate on work stress of millennial employees and the moderating effect of team-member exchange in the relationship between organizational climate and work stress of millennial employees. Participants are employees born in the time range of 1980 to 2000 and have worked for at least six months. This study utilized survey method with the instruments Stress Diagnostic Survey, Organization Climate Questionnaire, and Team-Member Exchange (TME) instrument which is a fusion of Team-Member Exchange Contributions and Team-Member Exchange Receipts. The data were analyzed with simple linear regression and moderation analysis utilizing the PROCESS module by Hayes. The results of this study indicate that organizational climate contributed negatively on the work stress of millennial employees. The higher the score for organizational climate, the lower the score for work stress on millennial employees. Team-member exchange cannot moderate the relationship between organizational climate and work stress of millennial employees. High quality of team-member exchange cannot strengthen the relationship between organizational climate and work stress of millennial employees. Penelitian ini bertujuan untuk mengetahui peran iklim organisasi terhadap stres kerja karyawan milenial dan efek moderator dari team-member exchange terhadap hubungan antara iklim organisasi dan stres kerja pada karyawan milenial. Partisipan adalah karyawan milenial dengan rentang tahun kelahiran 1980 hingga 2000 dan sudah bekerja minimal selama enam bulan. Penelitian ini menggunakan metode survei dengan instrumen Stress Diagnostic Survey, Organizational Climate Questionnaire, dan instrumen Team-Member Exchange (TME) yang merupakan gabungan dari Team-Member Exchange Contributions dan Team-Member Exchange Receipts. Analisis data menggunakan uji regresi linear sederhana dan uji moderasi dengan modul PROCESS dari Hayes. Hasil penelitian ini menunjukkan bahwa iklim organisasi berkontribusi negatif terhadap stres kerja karyawan mileneal. Semakin tinggi skor iklim organisasi, maka semakin rendah skor stres kerja karyawan milenial. Team-member exchange tidak dapat memoderasi hubungan antara iklim organisasi dan stres kerja karyawan milenial. Kualitas team-member exchange yang tinggi tidak dapat memperkuat hubungan iklim organisasi dengan stres kerja karyawan milenial.